A new improvement proposal to estimate regional input-output structure using the 2D-LQ approach - Rubén Martínez-Alpa\~nez; José Daniel Buendía Azorín; María del Mar Sánchez de la Vega (Economies, 2023)
The use of location quotients for the estimation of regional input-output tables has been found to be a useful and efficient tool to estimate intraregional production coefficients and multipliers. This paper considers some regionalisation methodologies based on location quotients for the estimation of input-output tables-some of which have hitherto not been analysed at the regional level-and studies which one provides the best estimation (best goodness of fit). We focus the analysis mainly on the accuracy of Flegg's location quotient (FLQ) and two-dimensional location quotient (2D-LQ). The analysis makes use of the multiregional input-output table for Korea for the year 2015 to evaluate the accuracy of the 2D-LQ method against FLQ. A novel proposal for the determination of the parameters corresponding to the 2D-LQ method is presented. This proposal is evaluated in Korean regions and is also applied to Spanish regions. The results obtained from the research conclude the general superiority of the 2D-LQ method, thus corroborating the results of other studies at the national level as well as the validity of our proposal.
Keywords: 330; 2D-LQ; FLQ; interregional trade flows; location quotients; regional input-output models; regression analysis